Phosphorus : an outline of its chemistry, biochemistry, and technology - Corbridge, D. E. C.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier Scientific Pub. Co., 1980)
Studies in Inorganic Chemistry 2, Phosphorus: An Outline of Its Chemistry, Biochemistry and Technology, Second Edition deals with the organic, inorganic, biochemical, physical, environmental, and technical aspects of phosphorus chemistry.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Phosphorus compounds; Organophosphorus compounds; Organophosphorus compounds; Phosphorus compounds; Phosphore -- Composés.; Phosphore -- Biochimie; Electronic books